Re-scripting the nation in 'post truth' era: the Indian story. Issue 1 (2nd January 2022) - Ranganathan, Maya
ABSTRACT: This paper evaluates the ways in which new national narratives are sought to be constructed in 'post-truth' era – marked by what Harsin terms competing convictions, discord and confusion and attempts to manage the communication environment. New technologies and online spaces facilitate the 're-creation' and 're-construction' of the past and are co-opted in the nation building project. In the context of extensive studies on how the democratic potential of new technologies is subverted, this paper calls for specific attention to the ways in which (imprecise) history forms part of discursive nationalism in present times. Taking up India as a case study, the paper explores and evaluates the strategies employed in the rescripting of the national narrative potentially leading to new national memory.